DESCRIPTION OF PHYSICAL ACTIVITY AMONG MIDWIFERY STUDENTS - Daryanto, Daryanto; Wulansari, Dasih Ayu; Putri, Tesa Samudra; Daryanti, Menik Sri (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Physical activity includes all movements, ranging from daily activities, moving from one place to another, work-related activities, and physical activities of low, moderate, and high intensity. Women in Indonesia tend to have a sedentary lifestyle or engage in physical activities at a low-intensity level. This study aims to describe the physical activity of midwifery students at Universitas ‘Aisyiyah Yogyakarta. This research employs a quantitative method with a cross-sectional approach. The sample consists of 52 midwifery students selected through purposive sampling. Data collection was conducted using a questionnaire, and data analysis utilized univariate analysis. The results indicate that most midwifery students at Universitas ‘Aisyiyah Yogyakarta engage in moderate physical activity, with 26 respondents (50%), while the least engage in high-intensity physical activity, with only 6 respondents (11.5%). It is recommended that students increase their physical activity, particularly through exercise.